An Analysis of Macro-processes in History: Some Thoughts on the Issues of Connecting Sociological and Historiographical Methods in Studying Religious History - Horský, Jan (Lidé města, 2009)
The study consists of (a) a methodological reflection of the theories of macro-processes and the possibilities of applying macro-analysis in history. It finds that the utilisation of macro-analysis in historical science is productive if theories of processes are applied on historical phenomena, which are studied chiefly as unintentional, and if we concentrate on selected sections, levels and segments (subcultures, formalised discursive modes, demographical phenomena etc.) of socio-cultural reality. The study presents (b) some elements of the development of the relationship between Czech historiography and sociology (the sociology of religion). It mentions the long-term problems of the relationship between the two. The study shows examples (c) of the work of several young historians, which show the possibility of the productive connection of sociology and history. The study argues in favour of macro-analytical methods in historiography that allow the connection of the methods of historical sociology with some of the elements of Anthropological History, New Cultural History and New Intellectual History. It also tries to show the development of the stands of Czech historiography on sociology (event. the historical sociology of religion) on the example of selected issues (the possibility of "objectively" identifying the "religious character" of social processes; the issues of religious homogeneity of traditional societies in relation to the so-called „paradigm of confessionalisation“; the discussion on the „disenchantment of the world“) and thus sketches the possibility of the socio-historical analysis of Czech religious history.